2020
DOI: 10.1136/bmjopen-2019-029159
|View full text |Cite
|
Sign up to set email alerts
|

Randomised controlled trial to investigate the relationship between mild hypercapnia and cerebral oxygen saturation in patients undergoing major surgery

Abstract: ObjectivesThe effects of hypercapnia on regional cerebral oxygen saturation (rSO2) during surgery are unclear. We conducted a randomised controlled trial to investigate the relationship between mild hypercapnia and rSO2. We hypothesised that, compared with targeted normocapnia (TN), targeted mild hypercapnia (TMH) during major surgery would increase rSO2.DesignA prospective, randomised, controlled trial in adult participants undergoing elective major surgery.SettingA single tertiary centre in Heidelberg, Victo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
16
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 47 publications
4
16
1
Order By: Relevance
“…Excluding the impacts of other relevant factors, blood dilution during CPB causes reductions in hematocrit and Hb, and insufficient blood oxygen-carrying capacity directly lowers the oxygen supply to the brain tissue. Here, Group H had a significantly higher rSO 2 (P<0.05), indicating that PHC is conducive to improving the autoregulation of the cerebral blood flow and the cerebral oxygen supply/consumption balance, which is consistent with a previous study (7). The reason may be that since CO 2 is the most effective regulator of cerebral blood flow, the PHC ventilation strategy in the patients undergoing CVR increases PaCO 2 , catalyzes the activity of neuronal nitric oxide synthase, increases nitric oxide production, causes the expansion of cerebral blood vessels, and increases cerebral blood flow and cerebral oxygen supply, thereby reducing the risk of cerebral ischemia and hypoxia and effectively protecting brain function (14).…”
Section: Comparison Of Mmse Scores At Each Time Point Between the Two Groupssupporting
confidence: 92%
See 1 more Smart Citation
“…Excluding the impacts of other relevant factors, blood dilution during CPB causes reductions in hematocrit and Hb, and insufficient blood oxygen-carrying capacity directly lowers the oxygen supply to the brain tissue. Here, Group H had a significantly higher rSO 2 (P<0.05), indicating that PHC is conducive to improving the autoregulation of the cerebral blood flow and the cerebral oxygen supply/consumption balance, which is consistent with a previous study (7). The reason may be that since CO 2 is the most effective regulator of cerebral blood flow, the PHC ventilation strategy in the patients undergoing CVR increases PaCO 2 , catalyzes the activity of neuronal nitric oxide synthase, increases nitric oxide production, causes the expansion of cerebral blood vessels, and increases cerebral blood flow and cerebral oxygen supply, thereby reducing the risk of cerebral ischemia and hypoxia and effectively protecting brain function (14).…”
Section: Comparison Of Mmse Scores At Each Time Point Between the Two Groupssupporting
confidence: 92%
“…The POCD incidence also differed significantly between the two groups at 24 h after surgery PHC is an important lung-protective ventilation strategy, as it not only increases PaCO 2 within an acceptable range, reduces tidal volume, "allows" hypercapnia, and prevents lung damage from high tension but also has protective and anti-inflammatory effects on the heart, nervous system, and many other organs (5,6). A previous study (7) showed that mild hypercapnia (PaCO 2 at 45-55 mmHg) increased rSO 2 , improved cerebral oxygenation, and reduced the incidence of POCD. The decrease in intraoperative rSO 2 is significantly associated with early POCD.…”
Section: Comparison Of Mmse Scores At Each Time Point Between the Two Groupsmentioning
confidence: 91%
“…In addition to MAP, PaCO 2 affects rSO 2 and V-MCA. Mild hypercapnia dilated the cerebral blood vessels and increases cerebral blood flow and is associated with the increase in rSO 2 from the baseline [ 46 , 47 ]. PaCO 2 , V-MCA, and rSO 2 were higher after SM than after RM ( Table 2 ); hence, we deduced that the changes in V-MCA and rSO 2 may be associated with the hypercapnia caused by ventilation pause.…”
Section: Discussionmentioning
confidence: 99%
“…Additional subgroup analysis established stronger evidence for targeted mild hypercarbia use. Few prospective studies [ 35 ] investigating the effects of targeted mild hypercarbia on rSO 2 during major surgery have confirmed similar effects.…”
Section: Discussionmentioning
confidence: 95%